School Health and Nutrition in Sri Lanka - World Bank (Washington, DC, 2015)
School health and nutrition (SHN) programs are critical for achieving education for all (EFA) as research has shown that improvements in health status contribute to improvements in learning and academic outcomes. Through programs targeted to address major health conditions that are highly prevalent among poor schoolchildren, (for example, iron deficiency anemia, hunger, worm infections, diarrheal disease, and malaria) SHN programs can have a large impact on children’s education, increasing the time that they spend at school and their ability to learn while at school. SHN programs are recognized as important educational policy initiatives to improve education outcomes. Furthermore, schools provide an excellent platform for the delivery of child health and nutrition services, where they can strengthen the cost-effectiveness of health interventions and deliver gains in participation and learning. In this paper, the policy platform is documented as well as the type, coverage, and the effect of the SHN interventions, followed by the key areas identified for development and learning of the school health promotion program (SHPP).